The Phenomenology of the Hunted Past: A Critical Synthesis and Rhetorical Reconstruction of Postcolonial Trauma in The Kite Runner - Karrar Haydar Zachi; Shuhaib, Mahdi (مجلة الباحث, 2026)
In Khaled Hosseini's The Kite Runner, the past hunts the postcolonial subject across time and space. This study uses the ‘hunted past’ theory to examine trauma in a society split by imperial interference and domestic colonization. Instead of seeing the flashback as a static symptom, this study proposes that the ‘hunted past’ is a narrative mechanism that brings the ‘silenced’ history of ethnic erasure into the present through guilt. Frantz Fanon's postcolonial psychopathology and Cathy Caruth's traumatic belatedness theory are used to critique the novel's Pashtun-Hazara division as a ‘Manichean’ fissure. It claims that Amir's betrayal of Hassan is a ritualistic replay of Afghanistan's structural ethnic hierarchies—a ‘micro-colonialism’ where the favored subject sacrifices the subaltern to survive. The ‘Great Game,’ the Soviet invasion, and the Taliban ascendancy have left the Afghan mentality structurally ‘unhomed,’ generating a diasporic condition marked by a continual flight from history, according to the research. Importantly, this study challenges the novel's redemption narrative. It shows the text's ideological blind spots—the marketing of Afghan pain for Western consumption and the blatant erasure of the female subaltern—by rigorously criticizing ‘auto-Orientalism’ and gendered silence. The story seeks reconciliation by rescuing the future generation, but the ‘hunted past’ resists assimilation. The research reveals that redemption for postcolonial subjects is a risky negotiation with a history that refuses to be buried.